Robot-assisted minimally invasive esophagectomy (RAMIE) compared to conventional minimally invasive esophagectomy (MIE) for esophageal cancer: a propensity-matched analysis - Tagkalos, E; Goense, L; Hoppe-Lotichius, M; Ruurda, J P; Babic, B; Hadzijusufovic, E; Kneist, W; van der Sluis, P C; Lang, H; van Hillegersberg, R; Grimminger, P P (Diseases of the esophagus, 2020)
SUMMARY Robot-assisted minimally invasive esophagectomy (RAMIE) is increasingly being applied as treatment for esophageal cancer. In this study, the results of 50 RAMIE procedures were compared with 50 conventional minimally invasive esophagectomy (MIE) operations, which had been the standard treatment for esophageal cancer prior to the robotic era. Between April 2016 and March 2018, data of 100 consecutive patients with esophageal carcinoma undergoing modified Ivor Lewis esophagectomy were prospectively collected. All operations were performed by the same surgeon using an identical intrathoracic anastomotic reconstruction technique with the same perioperative management and pain control regimen. Intra-operative and postoperative complications were graded according to definitions stated by the Esophagectomy Complications Consensus Group. Data analysis was carried out with and without propensity score matching. Baseline characteristics did not show significant differences between the RAMIE and MIE group. Propensity score matching of the initial group of 100 patients resulted in two equal groups of 40 patients for each surgical approach. In the RAMIE group, the median total lymph node yield was 27 (range 13–84) compared to 23 in the MIE group (range 11–48), P = 0.053. Median intensive care unit (ICU) stay was 1 day (range 1–43) in the RAMIE group compared to 2 days (range 1–17) in the MIE group (P = 0.029). The incidence of postoperative complications was not significantly different between the two groups (P = 0.581). In this propensity-matched study comparing RAMIE to MIE, ICU stay was significantly shorter in the RAMIE group. There was a trend in improved lymphadenectomy in RAMIE.